Heterozygous deletion of 10q24.31-q24.33– a new syndrome associated with multiple congenital anomalies: case report and literature review - Anastasiia A. Buianova; Yulia S. Lashkova; Tatiana V. Kulichenko; Ivan S. Kuznetsov; Artem A. Ivanov; Olga P. Parshina; Oleg N. Suchalko; Svetlana S. Vakhlyarskaya; Dmitriy O. Korostin (Neurological Research and Practice)
Abstract Background Congenital anomalies and neurodevelopmental disorders are complex conditions often requiring comprehensive diagnostic approaches. Next-generation sequencing (NGS), particularly whole-exome sequencing (WES), has greatly improved the detection of pathogenic variants, including copy number variations (CNVs), which account for up to 35% of genetic causes in neurological patients. Combining CNV and single nucleotide variant (SNV) analysis through WES enhances diagnostic accuracy, especially in cases with unclassified congenital anomalies. Case presentation and literature review This study reports a 14-year-old male patient with multiple congenital anomalies, including hypospadias, complete cleft palate, and recurrent pneumonia. His clinical presentation includes significant physical and intellectual developmental delays, autism-like symptoms, and spastic diplegia. Whole-exome sequencing (WES) was performed due to these complex symptoms, revealing a novel heterozygous deletion on chromosome 10q24.31-q24.33. Laboratory findings indicated agammaglobulinemia, leading to prophylactic antibiotic therapy and immunoglobulin replacement. Additional imaging studies showed cystic malformation of the middle lobe of the right lung, sliding hiatal hernia with prolapse of the gastric mucosa, and brain anomalies consistent with Joubert syndrome. Conclusions This case underscores the importance of genetic analysis in understanding the etiology of congenital anomalies and neurodevelopmental disorders, providing critical insights into the molecular mechanisms driving complex phenotypes. The identified chromosomal deletion contributes to the existing literature on genomic imbalances associated with similar phenotypes.